2006
DOI: 10.2307/20063313
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Technology-Enhanced Language Learning on Second Language Composition

Abstract: , 189 pp., 27 tables, references, 170 titles. Today's global culture makes communication through writing in a foreign language a most desirable tool to expand personal and professional relations. However, teaching writing is a complex, time-consuming endeavor in any language. Foreign language teachers at every level struggle to fit writing into an already full curriculum and need the most effective methods and tools with which to teach. Technology may provide a viable scaffold to support writing instruction fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Likewise, Oxford's (2004) study found that virtual tools could help students enhance their communication competence in the second language-learning environment. Accordingly, through…”
Section: Technology Enhanced Language Learning Environmentmentioning
confidence: 94%
“…Likewise, Oxford's (2004) study found that virtual tools could help students enhance their communication competence in the second language-learning environment. Accordingly, through…”
Section: Technology Enhanced Language Learning Environmentmentioning
confidence: 94%
“…Virtual interactions between students and educators promote "greater cognitive flexibility" (Wolfe, 2001, p. 6), which can enable students to interact in a less intimidating and socially oriented atmosphere. It can also enhance the dissemination of knowledge to a wider community of learners (Jeong & Frazer, 2008;Ng'ambi, 2003;Oxford, 2006). Here, learning is depersonalised, inviting the shy and marginalised-who are often intimidated by their classmates-to add their voices to discussions on teaching and learning (Maier & Warren, 2000;Martin & Madigan, 2006).…”
Section: Enhancing the Teaching And Learning Of Communication Skills 87mentioning
confidence: 99%
“…A word-processing program is one of the examples of the technology in language learning (Alsulami, 2016;Oxford, 2004;Walker & White, 2013). Kasapoglu-Akyol (as cited in Alsulami, 2016) said that using this program is a great method to assist students' writing development.…”
Section: Introductionmentioning
confidence: 99%